The Relationship Between Postoperative Pain Intensity and Sleep Quality in Patients After Spinal Anesthesia - shelina , shelina; Susanto, Amin; Burhan, Asmat (Java Nursing Journal, 2025)
Background: Postoperative pain in each patient will experience different pain from one another. Inadequate pain management can have a direct impact on postoperative pain, which is disruption of sleep quality. Purpose: The purpose of this research was to identify any correlation between the severity of postoperative pain and the quality of sleep experienced by patients after spinal anesthesia. Methods: This research employs a cross-sectional design based on quantitative correlation. Using a non-probability purposive sampling approach, 51 participants were surveyed after spinal anesthesia for this investigation. The data was collected in the inpatient room at Wijayakusuma Purwokerto Hospital using questionnaire sheets from the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and NRS (Numeric Rating Scale) to quantify postoperative pain severity. The Spearman rank test was used to examine the data. Results: Forty-three people (78.4% of the total) reported minor postoperative discomfort, while forty-three people (84.3% of the total) reported satisfactory sleep quality. A correlation force of 0.756 and a p-value of 0.000 were determined using the Spearman rank test. Conclusions: Patients undergoing spinal anesthesia at Wijayakusuma Purwokerto Hospital reported significantly higher levels of postoperative discomfort and worse sleep quality.